Increased incidence of adult pneumococcal pneumonia during school holiday periods - Daniel, Priya; Rodrigo, Chamira; Bewick, Thomas; Sheppard, Carmen; Greenwood, Sonia; McKeever, Tricia M.; Slack, Mary; Lim, Wei Shen (European Respiratory Society, 2017)
Child contact is a recognised risk factor for adult pneumococcal disease. Peaks in invasive pneumococcal disease incidence observed during winter holidays may be related to changes in social dynamics. This analysis was conducted to examine adult pneumococcal community-acquired pneumonia (CAP) incidence during school holiday periods.Between September 2008 and 2013, consecutive adults admitted to hospitals covering the Greater Nottingham area with a diagnosis of CAP were studied. Pneumococcal pneumonia was detected using culture and antigen detection methods.Of 2221 adults studied, 575 (25.9%) were admitted during school holidays and 643 (29.0%) had pneumococcal CAP. CAP of pneumococcal aetiology was significantly more likely in adults admitted during school holidays compared to term time (35.3% versus 26.7%; adjusted OR 1.38, 95% CI 1.11–1.72, p=0.004). Over the 5-year period, the age-adjusted incidence of hospitalised pneumococcal CAP was higher during school holidays compared to term time (incident rate ratio 1.35, 95% CI 1.14–1.60, p<0.001); there was no difference in rates of all-cause CAP or non-pneumococcal CAP. Reported child contact was higher in individuals with pneumococcal CAP admitted during school holidays compared to term time (42.0% versus 33.7%, OR 1.43, 95% CI 1.00–2.03, p=0.046).Further study of transmission dynamics in relation to these findings and to identify appropriate intervention strategies is warranted.School holiday periods are associated with an increased incidence of adult pneumococcal community-acquired pneumonia http://ow.ly/JiAb3089Gii%U http://openres.ersjournals.com/content/erjor/3/1/00100-2016.full.pdf